THE DEVELOPMENT OF PRINCIPAL LEADERSHIP MODEL AT INTERNATIONAL BACCALAUREATE SCHOOLS IN THAILAND - Subrahmanya, Ambika; Mhunpiew, Nathara (Scholar: Human Sciences, 2015)
The main aim of this study was to identify principal leadership responsibilities to develop principal leadership model at International Baccalaureate schools in Thailand. Transformational and instructional leadership approaches along with both qualitative and quantitative elements from the research were used to create the model. The data was gathered from 145 teachers from IB authorized international schools in quantitative approach and three principals were interviewed in qualitative approach. The results from the average mean showed that there is significant difference between current and desirable practices of principals at IB schools. Thirteen responsibilities out of twenty one responsibilities were significantly different. The data from the interview method were analyzed by constant comparative method and the findings revealed four leadership dimensions along with four domains. They were mentioned as factors for student academic achievement by Marzano (2005). Results of this study confirmed the findings from the literature that student academic achievement is the result of great leadership by responsible principal.